Video Clinics for Nasal Bone Injuries in COVID Times - Is it a Valid Tool for Routine Practice? - Ved Narang; Megan McGlone; Nick Calder (International Archives of Otorhinolaryngology)
Introduction We previously investigated the impact of video clinics on the management of closed nasal bone injuries during the coronavirus disease 2019 (COVID-19) pandemic. The aim of that study was to assess the feasibility of managing patients at their homes or workplaces, with instructions to attend outpatient clinics the next working day if they suspected any deviation or reduced nasal airflow, for further evaluation.